The literary guide & companion to southern England - Cooper, Robert M. (Ohio University Press, 1998)
"This newly revised and updated edition of Robert Cooper's acclaimed handbook combines the utility of current travel information with the appeal of literary history, biography, and anecdote in a leisurely and flavorful guide to the broad sweep of southern England outside of London. A rich and reliable guide to the landscape that fostered one of our most cherished cultures, The Literary Guide and Companion to Southern England is an indispensable resource for those who wish to experience literature firsthand."--Jacket.